A periodic pattern of SNPs in the human genome - Madsen, Bo Eskerod (Cold Spring Harbor Laboratory Press, 2007)
By surveying a filtered, high-quality set of SNPs in the human genome, we have found that SNPs positioned 1, 2, 4, 6, or 8 bp apart are more frequent than SNPs positioned 3, 5, 7, or 9 bp apart. The observed pattern is not restricted to genomic regions that are known to cause sequencing or alignment errors, for example, transposable elements (SINE, LINE, and LTR), tandem repeats, and large duplicated regions. However, we found that the pattern is almost entirely confined to what we define as “periodic DNA.” Periodic DNA is a genomic region with a high degree of periodicity in nucleotide usage. It turned out that periodic DNA is mainly small regions (average length 16.9 bp), widely distributed in the genome. Furthermore, periodic DNA has a 1.8 times higher SNP density than the rest of the genome and SNPs inside periodic DNA have a significantly higher genotyping error rate than SNPs outside periodic DNA. Our results suggest that not all SNPs in the human genome are created by independent single nucleotide mutations, and that care should be taken in analysis of SNPs from periodic DNA. The latter may have important consequences for SNP and association studies.